The analysis of the frequency of detection of congenital heart disease of the fetus in carryingout of penatal diagnosis in the Zaporozhye region - N. V. Avramenko; O. A. Nikiforov (Zaporožskij Medicinskij Žurnal)
In the clinic of Zaporozhye regional center of human reproduction at the prenatal formal care conferences for the period 2011-2012years was examined 1139 pregnant. All the examination in the prenatal formal care conferences during this period diagnosed 177 cases of congenital malformations of the heart. The age of the pregnant women have been registered cases of congenital heart diseases of the fetus, varied from 18 to 45 years. Risk factors for the development of fetal cardiac pathology were a viral infection in the 1st trimester of pregnancy at 13 pregnant(7,3%), the accompanying intrauterine infection in 5 (2,8%), weighed down by the course of pregnancy and complicated obstetric-gynaecological history had 16 (9%), mother’s age older than 35 years in 39 (22%), occupational hazards in 8 (4,5%) of the studied. The most frequent percentage of detection of congenital heart defects in the fetus would be the second trimester of pregnancy (62,2%), the minimum of the first trimester (4%). The most common form of congenital heart diseases of the fetus is a defect of the ventricular septum. Total atrioventricular canal diagnosed at 8.5% of the cases and refers to a heavy vices, which is an indication for abortion and is combined with chromosomal pathology in 26,6% of cases, which is an indication for abortion.